Diesel fuel spray penetration, heating, evaporation and ignition: modelling vs. experimentation. (20th June 2008) - Sazhin, S.S.; Martynov, S.B.; Kristyadi, T.; Crua, C.; , M.R. Heikal
The modified WAVE droplet breakup model, taking into account the transient processes during spray injection, the Effective Thermal Conductivity (ETC) liquid phase model, the gas phase model suggested by Abramzon and Sirignano, and the customised version of the Shell autoignition model have been implemented into the KIVA 2 CFD code. The observed Diesel spray tip penetration and Sauter Mean Radii show much better agreement with the prediction of the modified WAVE model compared with other droplet breakup models. The difference in the autoignition delay times predicted using the Infinite Thermal Conductivity (ITC) and ETC models is important for practical computations.